CONTRIBUTIONS OF GENETICS TO BANANA CULTIVATION: SYNTHESIS - Schlotag Stremel, Jonas (Journal of Interdisciplinary Debates, 2023)
Today, bananas and plantains play a leading role as primary sources of food and income generation in various regions of Brazil and the world. However, the incessant search for varieties that are resistant to adversity and have favorable agronomic characteristics, in line with market demands, is one of the main challenges for the expansion and development of this crop. In order to find solutions to reverse this situation, the development of cultivars through genetic improvement processes, especially the technique of hybridization between varieties, has stood out as a promising alternative. These advances have provided encouraging results, especially when considering the laboratory production of in vitro seeds. Against this backdrop, the main aim of this paper is to present a concise account of how the evolution of genetic improvement practices, together with related research, has contributed significantly to the transformation of the characteristics of bananas that we find today.